Migration and HIV/AIDS in Rural South Africa: A dual-phase intergenerational, gendered chain migration - Plowright, Alexandra; Hundt, Gillian; Stuttaford, Maria (African Human Mobility Review, 2021)
Migration is a complex process that is fundamental in understanding the complexity of societies across the world. In South Africa, there are high levels of migration associated with HIV and AIDS, and the process is intrinsically linked with issues associated with population health. Research conducted in KwaZulu-Natal Province, and in the wider country, has reported on a circular migratory flow of women to and from the province. However, this paper presents findings suggesting that the gendered migration occurring in this area is actually an intergenerational process of chain migration that involves women of different generations moving to South Africa from households in other southern African countries. Younger women are initially motivated to move by various push and pull factors, such as economic or environmental instability. Despite enthusiasm to move and motivation to succeed in South Africa, their experiences of migration to South Africa are mostly characterised by negativity. Often exposed to unsafe conditions coupled with a lack of opportunities for meaningful work, many are left vulnerable to HIV contraction. Older women then migrate to follow their daughters in response to requests for support, forming the second phase of this process of intergenerational chain migration. As a result of this process, which is strongly influenced by HIV, there are emerging communities of younger women who require access to services for HIV, and older women who are in need of primary care services associated with ageing while they are providing assistance to their kin and new host communities.